Review of The Effect of Erbium and Neodymium on Microstructure and Mechanical Properties of Magnesium Alloy - Ahmad, Rosli; Nor Azman, Muhammad Faez (Research Progress in Mechanical and Manufacturing Engineering, 2020)
For this study, the effect of the rare earth element erbium (Er) and neodymium (Nd) on the microstructure and mechanical properties of the Mg alloy investigated. The case study method performed by referring to previous research and journal articles. In the references, the experiments were performed by using optical microscopy (OM) and scanning electron microscopy (SEM) with electron dispersive spectroscopy (EDS) showed the erbium and neodymium altered the grain size of the alloys. The grain size of the alloys by observation on optical microscopy promised a grain refinement. SEM/EDS results showed that Er and Nd addition gave a new formation of intermetallic phases along the grain boundaries and dissolved into the magnesium matrix. Both additives improved the ultimate tensile strength (UTS) and the hardness value of the Mg-Zn base alloys.